PENDAMPINGAN DAN PENGENALAN PEMBUATAN ALAT TANGKAP IKAN BAGI SISWA SMA/SMK DI WILAYAH PESISIR KOTA KUPANG - Saraswati, Suprabadevi; Tallo, Ismawan (Program Studi Budidaya Perairan Universitas Mataram, 2022)
The waters of Kupang Bay have abundant fish potential. Some of the fishing gear operating in Kupang Bay which are classified as less environmentally friendly are the bagan fishing gear. To address these problems in an effort to preserve fish resources, it is necessary to pay attention to aspects of fishing technology used in accordance with responsible fisheries management (Code of Conduct for Responsible Fisheries/CCRF). Seeing that the fishing technology applied by the community is still traditional, so it is necessary to find other alternatives to improve fishing technology and methods so that the fish caught are only suitable target fish, it is necessary to study the level of friendliness of some fishing gear. This service aims to socialize Assistance and Introduction of environmentally friendly fishing gear and provide information on innovation of fishing gear as fishing gear that targets large pelagic fish. And practice how to make and use fishing gear